The Influence of Financial Literacy and E-Wallet Usage on the Consumptive Behavior and Financial Behavior of Management Students at Pembangunan Panca Budi University - Dessy Natalia Sianipar; Noni Ardian; Aulia (CV. Doki Course and Training, 2026)
This research aims to analyze the influence of financial literacy and e-wallet usage on the consumption behavior and financial behavior of Management students at Panca Budi Development University. The development of digital financial technology encourages the increased use of e-wallets, which has the potential to influence the consumption patterns and financial management of students. This study uses a quantitative approach with a causal associative design. Data were collected thru a Likert scale questionnaire distributed to 71 respondents using a saturated sampling technique. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS. The research results show that financial literacy has a positive and significant effect on consumptive behavior (t-statistic = 3.208; p= 0.001) and financial behavior (t-statistic 2.680; p = 0.007), while the use of e-wallets also shows a positive effect on consumptive behavior (t-statistic 1.154; p = 0.000) and a significant effect on financial behavior (t-statistic 4.507; p = 0.000). Simultaneously, this model can explain 42.1% of the variance in consumptive behavior and 38.6% of the variance in financial behavior. These test results provide empirical evidence that although digital accessibility facilitates transactions, the depth of financial literacy serves as a crucial regulatory mechanism. The synergy between financial literacy and the use of digital payment technology together becomes a real determinant in converting the use of e-wallets from mere consumption instruments into tools for more rational and measurable financial management in the digital economy era.